Bibliometric Analysis of Socially Responsible Investment (SRI) - Fatimah Iskandar Putri (SMART Insight, 2021)
In the last few decades, socially responsible investment has become a topic that has been studied more and more. This study aims to analyze the literature on socially responsible investment by covering research trends and future research directions. A total of 1,218 articles from Scopus with publications ranging from 1979-2023 were analyzed using the VOSViewer software. The quantitative approach is used in the bibliometric analysis, and the qualitative approach is used in the literature study. The findings in this study include research clusters divided into four paths: the practice/implementation of socially responsible investments, the performance of socially responsible investments, the influence of investor knowledge on socially responsible investments, and the impact of socially responsible investments.